PENGEMBANGAN VIDEO TUTORIAL NAIL ART MOTIF MARBLE MENGGUNAKAN BLOOMING GEL UNTUK KELAS XI TATA KECANTIKAN KULIT DAN RAMBUT DI SMKN 1 SOOKO MOJOKERTO - Amanda Natasya Putri; Nia Kusstianti; Mutimmatul Faidah; Sri Dwiyanti (Jurnal Tata Rias, 2026)
Practical Nail Art learning requires instructional media that present procedural steps through structured visual representations. Based on observations conducted in Class XI of the Skin and Hair Beauty Expertise Program at SMKN 1 Sooko Mojokerto, the instructional media currently used in the learning process have not provided optimal visual demonstrations, making it difficult for students to understand the Marble Nail Art technique using Blooming Gel. This study aimed to: (1) describe the development stages of a Nail Art tutorial video on the Marble technique using Blooming Gel; (2) evaluate the quality of the developed instructional media; (3) analyze students' practical performance; and (4) identify students' responses to the developed media. This study employed the Research and Development (R&D) method using the 4D development model, which consists of the Define, Design, Develop, and Disseminate stages. The validation results indicated that the tutorial video achieved a very high level of feasibility, obtaining scores of 92.5% for the media aspect, 96.3% for the material aspect, and 87.5% for the language aspect, all of which were classified as highly feasible. Furthermore, the average student practical performance score reached 87.11%, with a learning mastery rate of 100%. The questionnaire results also showed that students' responses to the instructional media reached 91.02%, which was categorized as very good. Therefore, the Marble Nail Art tutorial video using Blooming Gel is considered appropriate for use as supporting instructional media in practical learning.